(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the role of teachers in shaping the discipline and manners of fourth-grade students at Kandelu Kutura State Primary School, as well as to identify the characteristics of students and the factors that hinder their development. The study uses a qualitative approach with observation, interviews, and documentation methods. The research subjects consisted of 20 fourth-grade students and one homeroom teacher. The research was conducted at Kandelu Kutura State Elementary School, West Wewewa District, on 6–8 August 2025. Data were collected through observation of learning activities, in-depth interviews with teachers, and supporting documentation, then analysed using qualitative descriptive analysis. The results showed that the role of teachers in shaping discipline and manners was carried out through setting an example, habit formation, enforcement of rules, and giving advice. However, the students’ discipline and manners have not developed optimally, as evidenced by tardiness, late submission of assignments, lack of neatness in dress, and low use of polite language and mutual respect. The main inhibiting factors include students’ habits outside of school, lack of parental supervision, and consistency in enforcing rules